Anger in Cardiovascular Disease: Its Relationship with Depression and Anxiety Levels - Dilek, Avci; Kevser, Tari Selcuk; Emre, Ciydem; Gonul, Yilmaz Dundar (University of Pardubice, 2018)
Introduction: Psychiatric problems accompanying cardiac problems are noteworthy risk factors as regards cardiovascular morbidity and mortality. Aim: This study aimed to determine the anger level and anger expression style in patients with cardiovascular disease, and the association of anger level with anxiety and depression levels. Method: This cross-sectional study was conducted with 254 patients with cardiovascular disease. Study data were collected with the Personal Information Form, State-Trait Anger Expression Inventory, and Hospital Anxiety and Depression Scale. Descriptive statistics, the Kolmogorov- Smirnov test and Spearman correlation were used for the analysis. Results: The mean scores the patients obtained from the trait anger, anger-in, anger-out and angercontrol subscales were 24.28 ± 6.39, 18.37 ± 3.74, 16.78 ± 4.78, 18.65 ± 5.66 respectively. Trait anger level had a strong positive correlation with anxiety and depression levels. Anger-in level had a weak positive correlation with anxiety and depression levels. Anger-out level had a moderate positive correlation with anxiety and depression levels. On the other hand, anger-control level had a moderate negative correlation with anxiety level and a strong negative correlation with depression level. Conclusion: The participants’ anxiety and depression levels increased as their trait anger, anger-in and anger-out levels increased and their anger-control levels decreased. Therefore, in order to reduce anger levels of patients with cardiovascular disease, psychosocial interventions addressing anger control should be planned, and a multidisciplinary approach should be applied.
Keywords: anger; anxiety; cardiovascular disease; depression